Melatonin induces apoptosis through biomolecular changes, in SK‐LU‐1 human lung adenocarcinoma cells. (27th October 2014) - Plaimee, P.; Weerapreeyakul, N.; Thumanu, K.; Tanthanuch, W.; Barusrux, S.
Abstract Objectives Anti‐cancer effects of melatonin (N‐acetyl‐5‐methoxytryptamine, an indole‐amine), have been widely reported, however, little has been known, regarding its mechanism(s) of action in lung cancer. Thus, we investigated its induction of apoptosis through biomolecular changes (lipid, protein and nucleic acid/DNA) in the SK‐LU‐1 human lung cancer cell line. Materials and methods We used Fourier transform infrared (FTIR) microspectroscopy, and conventional methods, to confirm changes in lipid (annexin V/PI staining for membrane alteration), protein (caspase‐3/7 protein activity) and DNA (DAPI staining for DNA fragmentation). Results We observed from FTIR data that melatonin increased lipid content and reduced intensity of nucleic acid/DNA, confirmed by annexin V/PI and DAPI respectively. Secondary protein structure at 1656 cm−1 (α‐helix) was reduced and peak position of β‐sheet structure (1637 cm−1) was shifted to lower frequency. Alteration in apoptotic proteins was demonstrated via caspase‐3/7 activity induction. Conclusions High melatonin concentration exerted anti‐cancer effects by changing biomolecular structure of lipids, nucleic acids and proteins, supporting its enhancement of apoptotic induction.